To Study the Sensitivity and Specificity of Ankle Brachial Index in Diagnosis of Peripheral Arterial Disease in Diabetics With Coronary Artery Disease at a Large Tertiary Care Teaching Hospital (Global Journal of Medical Research, 2020)
The aim of study was to determine the sensitivity and specificity of ankle brachial index in diagnosis of peripheral arterial disease in diabetics with coronary artery disease at a teaching hospital in North India Materials and methods All diabetic patients admitted with coronary artery disease who undergo coronary angiography irrespective of their presentation stable angina unstable angina NSTEMI STEMI were included in the study Systolic blood pressures of both arms at the brachial arteries and both lower limbs at the dorsalis pedis arteries were taken with the help of sphygmomanometer and a hand held doppler probe and recorded in the proforma The higher of the two systolic pressures recorded at the ankle was divided by the highest of the systolic pressures recorded in the arms to get the ankle brachial index The results of ABI were compared with peripheral angiography
Keywords: ABI; ankle brachial Index: PAD; peripheral arterial disease